Emily Dickinson and Represented Buddhism in Nineteenth-Century America. Issue 2 (17th February 2017) - Kang, Yanbin
ABSTRACT: Dickinson's poetics engage in a lifelong conversation with Buddhism, indirectly through her reading of American writers' references to Buddhism. In her early years from 1860 to 1865, she tentatively practices the way towards Nirvana, represented as contemplative calm and subjugation of consciousness, or Nothing, albeit with some doubt; the metaphors about Nirvana shape her, redefining Heaven as a detached mind and constructing idiosyncratic images. The Buddhist vogue since the 1870s reinforces Dickinson's negative way of achieving peace, cultivates her aesthetics of emptiness and energises her slide into silence. This essay seeks to document the complex interaction between Dickinson and other Buddhism-inspired American writers, in the process revealing something about the formation of Dickinson's Eastern aesthetics. This discussion will also reveal how an approach informed by Buddhism will shed new light upon some of Dickinson's poems.